Hollow Zn/Co Zeolitic Imidazolate Framework (ZIF) and Yolk-Shell Metal@Zn/Co ZIF Nanostructures - Rösler, Christoph; Aijaz, Arshad; Turner, Stuart; Filippousi, Maria; Shahabi, Azar; Xia, Wei; Van Tendeloo, Gustaaf; Muhler, Martin; Fischer, Roland A. (Chemistry : a European journal, 2016)
Metal–organic frameworks (MOFs) feature a great possibility for a broad spectrum of applications. Hollow MOF structures with tunable porosity and multifunctionality at the nanoscale with beneficial properties are desired as hosts for catalytically active species. Herein, we demonstrate the formation of well‐defined hollow Zn/Co‐based zeolitic imidazolate frameworks (ZIFs) by use of epitaxial growth of Zn‐MOF (ZIF‐8) on preformed Co‐MOF (ZIF‐67) nanocrystals that involve in situ self‐sacrifice/excavation of the Co‐MOF. Moreover, any type of metal nanoparticles can be accommodated in Zn/Co‐ZIF shells to generate yolk–shell metal@ZIF structures. Transmission electron microscopy and tomography studies revealed the inclusion of these nanoparticles within hollow Zn/Co‐ZIF with dominance of the Zn‐MOF as shell. Our findings lead to a generalization of such hollow systems that are working effectively to other types of ZIFs. An easy and reproducible method to synthesize hollow Zn/Co ZIF nanostructures (see figure; NP = nanoparticle) in a two‐step protocol was developed. The strategy involves the targeted growth of a second ZIF on pre‐synthesized ZIF‐67 crystals with subsequent self‐sacrifice/excavation of ZIF‐67 to give nanocage‐like materials.